Economic forecast disagreement and equity pricing: International evidence - Mehran Akbari; Christian Bauer; Matthias Neuenkirch; Dennis Umlandt (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2025)
Economic expectations play a central role in financial markets, yet investors often disagree about the economy's future. This disagreement has long been viewed as a potential driver of asset prices, but it remains unclear whether it reflects mispricing or a priced source of risk. We address this question by constructing monthly disagreement indices from Consensus Economics forecasts from 24 OECD markets. Firm-level exposure to economic disagreement is estimated through return regressions. Results reveal pronounced cross-country heterogeneity. In developed markets, particularly the United States, greater exposure to disagreement consistently predicts lower future returns, supporting the mispricing hypothesis. Smaller markets exhibit mixed patterns, with some evidence of positive risk premia, while other cases show no significant effect. These findings provide new international evidence that the pricing of forecast disagreement is context-dependent, shaped by market structure and institutional depth.
Keywords: D84; G12; G14; G15; 330; Asset Pricing; Consensus Economics; Forecast Disagreement; Macroeconomic Forecasts